The policy of the Mamluks towards the Franks in the era of Shajar Al-Durr and Al-Mu'izz Ibek (648-655 AH / 1250-1257 AD) - زهرة, مازن; غادة حسن; بشار عباس (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
At the beginning of their state in Egypt, the Mamluks faced the danger of the Frankish presence in Damietta, in addition to the greatest danger, which was the Ayyubids in the Levant, who rejected the rule of the Mamluks, which led to the instability of the political situation in the region. To confront the Ayyubid threat, the Mamluks had to adopt a policy based on diplomacy and appeasement with the Franks and their leader at the time, Louis IX, King of France, residing in Acre, regarding outstanding matters between them. This research aims to trace the policy of the Mamluk sultans in the reigns of Shajar al-Durr and al-Muizz Aybak towards the Franks by tracing the course of embassies, negotiations and agreements signed between the two parties.